Analysis of the exception of the rule that the death penalty does not apply to the elder——take China for example - Zhang, Min-na (International Theory and Practice in Humanities and Social Sciences, 2025)
China has gradually entered an ageing society and crimes committed by the elderly have become a social problem that cannot be ignored. The Amendment of the Criminal Law (VIII) therefore provides for the application of the death penalty to the elderly that the death penalty is not applicable to the elderly in principle, but may be applied in exceptional circumstances. However, there are imperfections in this article, such as the unclear definition of "at the time of trial" and "causing death by particularly cruel means", the inappropriate setting of the starting point of "at the time of trial", and the lack of a definition of whether the death penalty is applicable to the elderly and whether it should be imposed. These issues need to be resolved in order to better apply this law. The act such as replacing "at the time of trial" with "at the time of the commission of the offence", lowering the definition of the age of the elderly to 70 years old, and giving priority to the application of suspended sentences to elderly people sentenced to death can be considered. This will help to better protect the rights and interests of the elderly, protect human rights and uphold social justice.